2017
DOI: 10.4025/actascibiolsci.v39i3.32095
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>In vitro</i> inactivation of thrombin generation by polysulfated fractions isolated from the tropical coenocytic green seaweed <i>Caulerpa racemosa</i> (Caulerpaceae, Bryopsidales)

Abstract: ABSTRACT. Pharmacological efficacy of Caulerpa racemosa (Chlorophyta) sulfated polysaccharidic (SPs) fractions (F I→III) on models of coagulation and inflammation has been demonstrated, but not their effects on thrombin generation (TG). This study examined fractions for composition and physicalchemical characteristics and in vitro inactivation of TG by F I and F II in 60-fold diluted human plasma using continuous method. Papain-extraction yield of 0.7% revealed F I→III by DEAE-cellulose chromatography, with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 32 publications
(126 reference statements)
0
13
0
Order By: Relevance
“…Fractions Cc-SP2 and Cc-SP3 primarily showed here electrophoretic mobilities compared to UHEP. These observations suggested that C. cupressoides produced other polysaccharides that were not detected after staining with toluidine blue alone (Volpi & Maccari, 2002;Salles et al, 2017;Rodrigues et al, 2017a;Rodrigues et al, 2017b).…”
Section: Analyses Of Sps Fractions By Physical-chemical Approaches Rementioning
confidence: 93%
See 4 more Smart Citations
“…Fractions Cc-SP2 and Cc-SP3 primarily showed here electrophoretic mobilities compared to UHEP. These observations suggested that C. cupressoides produced other polysaccharides that were not detected after staining with toluidine blue alone (Volpi & Maccari, 2002;Salles et al, 2017;Rodrigues et al, 2017a;Rodrigues et al, 2017b).…”
Section: Analyses Of Sps Fractions By Physical-chemical Approaches Rementioning
confidence: 93%
“…This anticoagulant action of Cc-SP2 was revealed to be 15 ± 0.3 IU mg -1 ( Figure 3A), whereas UHEP (193 IU mg -1 ) still altered the APTT test when a minimum concentration of 2.5 μg mL -1 (42.15 ± 0.60 s) was used (Salles et al, 2017;Rodrigues et al, 2017b) as inhibitor of the contact-pathway (p < 0.01) (Pomin, 2012;Mourão, 2015). As also expected, fractions Cc-SP1 and Cc-SP3 had no effect on APTT, when a high concentration of SPs (1 mg mL -1 ) was tested in vitro (p > 0.05) (data not shown) (Rodrigues et al, 2011a).…”
Section: Low-molecular-size Sps-containing Fractions From C Cupressomentioning
confidence: 98%
See 3 more Smart Citations